A nationwide analysis of 16 year trends in cardiac transplantation for acute myocarditis. (25th November 2020) - Isath, A; Perembeti, S; Correa, A; Haider, S; Ho, K; Rao, S; Chahal, A; Narasimhan, B; Padmanabhan, D; Garg, V; Contreras, J
Abstract: Background: Orthotopic heart transplant (OHT) is indicated in 1–8% of patients with myocarditis. However, national trends in the utilization of transplantation and outcomes in myocarditis across the United States are not well established. Purpose: Our objective was to study the trends and baseline characteristic of myocarditis patients undergoing heart transplant in the United States using Healthcare Cost and Utilization Project (HCUP) National (nationwide) Inpatient Sample (NIS) from 1999 to 2014. Methods: Using NIS data, we identified patients older than 18 years with myocarditis using codes ICD9 codes of 422.0 and 422.9. Among these patients, we identified those who underwent cardiac transplantation using ICD9 procedure codes 37.5 and 33.6. We presented categorical data as percentages and continuous data as mean or median as appropriate. Results: We identified a total of 62, 264 hospitalizations for myocarditis from 1999–2014. 430 (0.69%) myocarditis patients underwent OHT which consisted of 0.82% of all 29990 cardiac transplants identified in the same period. The trends in OHT for myocarditis is as shown in Figure 1. The mean age was 32.9±2.4 years and 51.1% (n=219) were females. 235 (54.6%) were Caucasians and 60 (13.9%) were Hispanic. Majority of the transplants were performed at medium (16%) and large sized hospitals (80.4%). Cardiac transplants were mainly done at teaching hospitals (98.9%). Further, with regards to the geographical distribution of transplant procedure, most were done in the West (37.2%) followed by South (25.3%), Northeast (21.4%) and Mid-west (16%) of the United States. Private insurance was the major payor source which covered 245 (58%) patients followed by Medicaid covering 112 (26%) patients. A total of 26 (6%) myocarditis patients died during the same hospitalization for OHT. In terms of discharge following OHT in myocarditis 85.8% (n=369) were discharged home and 8.1% (n=35) to short term hospitalization. The average length of stay for OHT for myocarditis was 64.3±6.3 days. Also, the mean cost of hospitalization for heart transplant in myocarditis when adjusted for inflation was 789, 566±93, 108 dollars. In-patient mortality following OHT was not significantly different in large sized hospital compared to small and medium sized hospitals (7.6% vs 5.7%, p=0.54). However, the cost of hospitalization was significantly lesser in small and medium sized hospitals (588, 363±154, 349 vs 826, 864±106, 110 dollars, p<0.0001). Conclusions: Only a small percentage of OHT is done for myocarditis with high proportion done in female when compared to OHT for other etiologies. Further studies need to be done to compare long term outcomes of heart transplant in myocarditis. Funding Acknowledgement: Type of funding source: None